Pola konsumsi dan investasi di Indonesia - Nugraha, Awang Aji; Nafi’a, Moh. Zidni Ilman; Pratama, Kevin Surya Aldi (Maliki Interdisciplinary Journal, 2024)
Consumption and investment are two important components that drive a country's economy. In Indonesia, there has been an increase in public consumption of durable goods and transportation services as well as ready-to-eat food. This reflects changes in lifestyles that are more consumerist driven by the increasing middle class and advances in digital technology. Meanwhile, in terms of investment, the products most in demand are mutual funds, shares, peer to peer lending, gold and property. Unfortunately, this increase in consumption has not been matched by adequate domestic investment growth, reflected in the low investment to GDP ratio. This condition risks causing various economic problems such as a current account deficit and slowing real sector growth. Therefore, appropriate policies are needed to direct consumption of domestic products while improving the investment climate, in order to achieve balanced consumption and investment patterns for the stability of the Indonesian economy in the future.and negative impacts on the economy, such as increasing demand, production and income, but also causes environmental problems, health and social inequality.